IMPLEMENTASI SISTEM LAYANAN ADMINISTRASI KEPENDUDUKAN ONLINE DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI DUKCAPIL KABUPATEN SUMBAWA - Winda Junita; Marisa Sutanty; Afina Aurellya Kamal (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the Effect the Implementation of the Online Service System (SILAMO) at the Dinas Kependudukan dan Pencatatan Sipil of Sumbawa District. The type of this study was associative study. The type of data used was quantitative data. The sources of data in the study were primary and secondary data. The numbers of population in this study were 35. The technique of determining sample was saturated sampling thus the number of samples in this study were 35. The tools used to collect data were questionnaires. The technique of data analysis was simple linear regression analysis through the assistance of the Statistical Product Service Solution (SPSS) program. Based on the results of data analysis, it is known that the t-statistic value was 5.970, which was greater than the t-table value of 2.034 (5.970>2.034), and the resulting significance value sebesar 0.000, which was smaller than 0.05 (0.000<0.05). Thus, it can be stated that the online service system (SILAMO) had a positive and significant effect on the quality of public services at the Dinas Kependudukan dan Pencatatan Sipil of Sumbawa District. The percentage effect of the Implementation of the Online Service System (SILAMO) at the Dinas Kependudukan dan Pencatatan Sipil of Sumbawa District was 74.9%, while the remaining of 25.1% was influenced by other variables outside this study, such as the competence and professionalism of officers, facilities and infrastructure, work systems and procedures, work environment, and public perceptions and expectations.